Analisis Pengaruh Jumlah Mata Pisau terhadap Daya dan Waktu pada Mesin Pengiris Bawang - Saputra, Ilham Dwi; Nurdin, Hendri; Sari, Delima Yanti; Adri, Junil (MASALIQ, 2024)
Shallot (Allium ascalonicum L) is a horticultural commodity classified as a spice vegetable. According to the Central Bureau of Statistics, shallot production in Indonesia in 2021 reached 2.01 million tons. This figure increased by 10.42 percent compared to the 2020 production which reached 189.15 thousand tons. Fried shallots are one of the processed forms of shallots which in the manufacturing process go through the slicing stage. Research on this onion slicing machine has been done a lot. Similar research discusses analyzing the development of a more efficient slicing machine. Things that must be considered in the process of making slicing machine construction are the number of blades, power consumption, time and slice results. The purpose of this research is to be able to analyze variations in the number of blades properly for onion slicing machines and find out their effect on power consumption, slicing time and slice results. This research uses the Experiment research method with the help of Microsoft Excel 2019 software. The results showed that the greater the variation in the number of blades, the lower the power consumption and slicing time and it was found that the level of damage to the sliced results was greater the more the number of blades. The conclusion of this research is that the greater the variation in the number of blades, the lower the power consumption and slicing time. The sharpness and length of the blade affect the results of sliced onions.